EDUCATIONAL AND METHODOLOGICAL SUPPORTS BY THE JADIDS IN PUBLICATION OF TEXTBOOKS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article analyzes the creation of textbooks and teaching aids for the new method schools, as well as the opinions of representatives of the Turkestan Jadidism about education. The author explored the futurological aspects of the ideas of enlightened Jadids about the effective use of the ideas of patriotism, diligence, literacy and tolerance for national development, as well as the factors that develop the country through innovative way of thinking.